5-alkylvinyl-1, 2, 4-triazole nucleosides: Synthesis and biological evaluation. (2nd July 2020) - Prutkov, Alexander N.; Chudinov, Mikhail V.; Matveev, Andrey V.; Grebenkina, Lyubov E.; Akimov, Mikhail G.; Berezovskaya, Yulia V.
Abstract: Some 5-substituted ribavirin analogues have a high antiviral and anticancer activity, but their mechanisms of action are obviously not the same as their parent compound. The SAR studies performed on 3 (5)-substituted 1, 2, 4-triazole nucleosides have shown a high dependency between the structure of the 3 (5)-substituent and the level of antiviral/anticancer activity. The most active substances of the row contain coplanar with the 1, 2, 4-triazole ring aromatic substituent which is connected by a rigid ethynyl bond. However, the compounds with the trans-vinyl linker also had antiviral activity. We decided to study the antitumor activity of ribavirin analogues with alkyl/aryl vinyl substituents in the 5th position of the 1, 2, 4-triazole ring. Protected nucleoside analogues with various 5-alkylvinyl substituents were obtained by Horner-Wadsworth-Emmons reaction from the common precursor and converted to the nucleosides. Arylvinyl nucleosides were synthesised according the reported procedures. All compounds did not show significant antiproliferative activity on several tumour cell lines. Coplanar aromatic motif in the 5-substituent for the anticancer activity manifestation was confirmed.